Application of low dose aspirin in pre-eclampsia - Ren, Yu; Zhao, Yong; Yang, Xiangdong; Shen, Chaojun; Luo, Hua (Frontiers in Medicine, 2023)
Aspirin is widely used in the primary and secondary prevention of cardiovascular and cerebrovascular diseases. Low-dose aspirin is also widely used to prevent pre-eclampsia and fetal growth retardation in utero. However, the use of aspirin during pregnancy is controversial. Since 1985, when aspirin was reported to be effective in obstetrics, numerous studies have attempted to determine the effect of low-dose aspirin on the morbidity of pre-eclampsia but have remained inconclusive. Guidelines for aspirin in preventing pre-eclampsia are different in different countries and regions. This article summarizes the research progress, mechanism, and application prospect of aspirin in preventing pre-eclampsia, providing a theoretical basis for the rational use of aspirin in pregnancy.